Saint Kitts and Nevis. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Kitts and Nevis during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as financing, greenhouse, technical support, epidemiological surveillance, veterinary medicine, protected agriculture, water management, use of pesticides, quarantine, production of flour and cassava.